High Resolution Electrochemical Imaging for Sulfur Vacancies on 2D Molybdenum Disulfide. Issue 3 (22nd January 2023) - Gu, Chaoqun; Sun, Tong; Wang, Zhenyu; Jiang, Sisi; Wang, Zonghua
Abstract: Molybdenum disulfide (MoS2 ) is considered as one of the most promising non‐noble‐metal catalysts for hydrogen evolution reaction (HER). To achieve practical application, introducing sulfur (S) vacancies on the inert basal plane of MoS2 is a widely accepted strategy to improve its HER activity. However, probing active sites at the nanoscale and quantitatively analyzing the related electrocatalytic activity in electrolyte aqueous solution are still great challenges. In this work, utilizing high‐resolution scanning electrochemical microscopy, optimized electrodes and newly designed thermal drift calibration software, the HER activity of the S vacancies on an MoS2 inert surface is in situ imaged with less than 20‐nm‐radius sensitivity and the HER kinetic data for S vacancies, including Tafel plot and onset potential, are quantitatively measured. Additionally, the stability of S vacancies over the wide range of pH 0−13 is investigated. This study provides a viable strategy for obtaining the catalytic kinetics of nanoscale active sites on structurally complex electrocatalysts and evaluating the stability of defects in different environments for 2D material‐based catalysts. Abstract : With optimized electrodes and newly designed thermal drift calibration software, it is possible to visualize and locate the nanoscale active sites formed by S vacancies on inert MoS2 basal plane by high‐resolution scanning electrochemistry microscopy. Moreover, the related hydrogen evolution reaction (HER) kinetics and the stability in different environments are quantitatively analyzed though this strategy.